Innovative swine blood hydrolysates as promising ingredients for European seabass diets: Impact on growth performance and resistance to Tenacibaculum maritimum infection - Resende, Daniela (2022)
Hydrolysates from high-protein coproducts are rich in bioactive peptides (small amino acid chains with properties beyond their nutritional value). When included in aquafeeds, they may promote fish robustness while increasing animal blood value and minimizing waste, contributing to a circular economy. This work assessed how innovatively produced blood hydrolysates (BH) included in plant-based diets for European seabass (Dicentrarchus labrax) affected growth performance and resistance to Tenacibaculum maritimum infection. Three fractions of swine BH obtained by autohydrolysis (AH) or enzymatically were selected. AH fraction was oven-dried, whilst the enzymatically obtained BH were further submitted to a micro (RMF) and nanofiltration (RNF) and the respective retentates freeze-dried. A commercially based diet was formulated, where 50% of fishmeal was replaced by vegetable proteins, and used as negative control (NC). Each BH fraction was then added at 3% to the NC and further compared to a fishmeal-based diet (positive control, PC); all diets remained isolipidic and isoproteic. Diets were assigned to triplicate groups of European seabass juveniles (12.3±1.4g) and fed three times daily until apparent satiation in a recirculating saltwater system. After a 12-week growth trial, fish were bath challenged with T. maritimum and cumulative mortality followed for 8days. A digestibility trial was also performed in parallel. Hydrolysates-containing diets had a significantly lower apparent digestibility coefficient (ADC) of dry matter compared to the PC, but RNF did not differ from the NC. RMF and AH had lower lipid ADCs than both controls, while the RNF only differed from the PC. Mineral ADCs of PC, NC and RNF were similar. Calcium ADC in RMF and AH was significantly lower than all other diets; RMF also displayed lower copper and potassium ADCs. Fish fed PC had the highest final weight, followed by NC and RNF. Daily growth index and feed conversion ratio (FCR) of RNF was similar to both controls. RMF induced the lowest final weight, highest FCR and reduced villus length in anterior intestine. This diet has also resulted in increased plasmatic peroxidase, but lower lysozyme, compared to all other treatments, showing the lowest disease resistance. Results clearly show that the RNF was the only test diet that significantly reduced European seabass mortality after T. maritimum infection, without affecting fish growth in relation to a practical plant-protein based diet, highlighting its high potential for aquafeeds supplementation.